Effect of ursodeoxycholic acid and vitamin E in the prevention of liver injury from methotrexate in pediatric leukemia - Bordbar, Mohammadreza; Shakibazad, Nader; Fattahi, Mohammadreza; Haghpanah, Sezaneh; Honar, Naser (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: Ursodeoxycholic acid (UDCA) and antioxidants such as vitamin E are considered to have a protective role in preventing chemotherapy-induced liver damage. The aim of this study was to assess the efficacy of these agents for hepatoprotection in pediatric patients with B-cell acute lymphoblastic leukemia (ALL), who were treated with methotrexate in their maintenance phase of treatment. Materials and Methods: Eighty children with B-cell ALL were randomly divided into four groups. Group 1 was administered oral vitamin E (400 mg/day); group 2 was administered oral UDCA (15 mg/kg/day); group 3 was administered a combination of the two drugs; and group 4 served as a control group and was administered no drug except their chemotherapy drugs. Complete blood count, liver function test, liver ultrasonography, and liver fibroscan were requested, and the results were compared. Results: Group 1 showed a slight increase in total bilirubin levels compared to baseline levels during the study (P=0.036). Group 2 showed a decline in aspartate aminotransferase and alanine aminotransferase levels during the study and at 6 months after discontinuing the drug; however, these differences were not statistically significant (P=0.051 and 0.083, respectively). None of the patients showed the evidence of significant fibrosis on liver fibroscan. Eight patients showed some evidence of mild-to-moderate fibrosis (F1, F2), but the results were not different between the groups as well as between pre- and post-study periods in each group. Conclusion: Low-dose methotrexate does not cause significant liver fibrosis in pediatric leukemia. UDCA and vitamin E have minimal roles in hepatoprotection among pediatric patients with ALL. Cite this article as: Bordbar M, Shakibazad N, Fattahi M, Haghpanah S, Honar N. Effect of ursodeoxycholic acid and vitamin E in the prevention of liver injury from methotrexate in pediatric leukemia. Turk J Gastroenterol 2018; 29: 203-9.